80
$\begingroup$

How can one prove this identity?

$$\frac{\zeta(2) }{2}+\frac{\zeta (4)}{2^3}+\frac{\zeta (6)}{2^5}+\frac{\zeta (8)}{2^7}+\cdots=1$$


There is a formula for $\zeta$ values at even integers, but it involves Bernoulli numbers; simply plugging it in does not appear to be an efficient approach.

$\endgroup$
  • 12
    $\begingroup$ I think this is a normal question. I don't know why "on hold"? $\endgroup$ – E.H.E Dec 24 '14 at 19:28
  • 2
    $\begingroup$ There is a recursive formula for $\zeta(2n)$ derived in this answer. However, in that answer it is shown that $$\sum_{k=1}^\infty\zeta(2k)x^{2k}=\frac12(1-\pi x\cot(\pi x))$$ With $x=\frac12$, this immediately gives $$\sum_{k=1}^\infty\zeta(2k)\left(\frac12\right)^{2k-1} =1-\frac\pi2\cot\left(\frac\pi2\right)=1$$ This is what is used in Random Variable's answer. $\endgroup$ – robjohn Dec 31 '14 at 18:13
113
$\begingroup$

Since $$\zeta(2n) = \frac{1}{(2n-1)!}\int_{0}^{+\infty}\frac{x^{2n-1}}{e^x-1}\,dx $$ we have: $$\sum_{n=1}^{+\infty}\frac{\zeta(2n)}{2^{2n-1}} = \int_{0}^{+\infty}\frac{\sinh(x/2)}{e^x-1}\,dx =\frac{1}{2}\int_{0}^{+\infty}e^{-x/2}\,dx = \color{red}{1}.$$

$\endgroup$
  • 2
    $\begingroup$ @mathworker21: I can mention that the dominated (or just monotone) convergence theorem clearly applies here. $\endgroup$ – Jack D'Aurizio Jul 14 '17 at 18:41
119
$\begingroup$

$$ \begin{align} \sum_{n=1}^\infty\frac{\zeta(2n)}{2^{2n-1}} &=\sum_{n=1}^\infty\sum_{k=1}^\infty\frac2{k^{2n}2^{2n}}\tag{1}\\ &=2\sum_{k=1}^\infty\sum_{n=1}^\infty\frac1{(4k^2)^n}\tag{2}\\ &=2\sum_{k=1}^\infty\frac1{4k^2-1}\tag{3}\\ &=\sum_{k=1}^\infty\left(\frac1{2k-1}-\frac1{2k+1}\right)\tag{4}\\[6pt] &=1\tag{5} \end{align} $$ Explanation:
$(1)$: expand $\zeta(2n)=\sum\limits_{k=1}^\infty\frac1{k^{2n}}$
$(2)$: change the order of summation
$(3)$: sum of a geometric series
$(4)$: partial fractions
$(5)$: telescoping sum

$\endgroup$
  • $\begingroup$ @robjohn, in $(3)$ the numerator should have a $4k^2$. $$\sum_{n=1}^{\infty} \frac{1}{(4k^2)^n} = \frac{1}{1- \frac{1}{4k^2}} = \frac{4k^2}{4k^2 - 1}$$ $\endgroup$ – Amad27 Mar 20 '15 at 16:45
  • 2
    $\begingroup$ @Amad27: Notice that the sum starts from $n=1$. This means that the sum is $\dfrac{\frac1{4k^2}}{1-\frac1{4k^2}}$. $\endgroup$ – robjohn Mar 20 '15 at 17:10
  • $\begingroup$ Ah! I couldn't catch the index! Sorry robjohn! $\endgroup$ – Amad27 Mar 20 '15 at 18:17
  • 4
    $\begingroup$ This one appears to be simplest possible answer. +1 It is as if you see the result in question at the level of $1 + r + r^{2} + \cdots = 1/(1 - r)$. $\endgroup$ – Paramanand Singh Jun 20 '16 at 10:29
  • $\begingroup$ Plain and simple - as always @robjohn :) $\endgroup$ – AD. May 23 at 7:43
38
$\begingroup$

The Laurent expansion of $\cot (z)$ at the origin in terms of the Riemann zeta function is $$ \cot (z) = \frac{1}{z} - 2 \sum_{k=1}^{\infty}\zeta(2k) \frac{z^{2k-1}}{\pi^{2k}} \ , \ 0 < |z| < \pi. $$

Letting $ \displaystyle z= \frac{\pi}{2}$, $$\cot \left(\frac{\pi}{2} \right) = \frac{2}{\pi} - \frac{2}{\pi} \sum_{k=1}^{\infty} \frac{\zeta(2k)}{2^{2k-1}}.$$

But $\cot \left(\frac{\pi}{2} \right)=0$.

Therefore,

$$ \sum_{k=1}^{\infty} \frac{\zeta(2k)}{2^{2k-1}} = 1.$$

$\endgroup$
11
$\begingroup$

$\newcommand{\angles}[1]{\left\langle{#1}\right\rangle} \newcommand{\braces}[1]{\left\lbrace{#1}\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack{#1}\right\rbrack} \newcommand{\dd}{\mathrm{d}} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,\mathrm{e}^{#1}\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{\mathrm{i}} \newcommand{\iff}{\Leftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left({#1}\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\root}[2][]{\,\sqrt[#1]{\,{#2}\,}\,} \newcommand{\totald}[3][]{\frac{\mathrm{d}^{#1} #2}{\mathrm{d} #3^{#1}}} \newcommand{\verts}[1]{\left\vert{#1}\right\vert}$

\begin{align} &\bbox[10px,#ffd]{\sum_{n = 1}^{\infty}{\zeta\pars{2n} \over 2^{2n - 1}}} = \sum_{n = 2}^{\infty}{\zeta\pars{n} \over 2^{n - 1}} - \sum_{n = 1}^{\infty}{\zeta\pars{2n + 1} \over 2^{2n}} \\[3mm] = &\ -\sum_{n = 2}^{\infty}\pars{-1}^{n}\zeta\pars{n}\pars{-\,\half}^{n - 1} - \sum_{n = 1}^{\infty}\bracks{\zeta\pars{2n + 1} - 1}\pars{\half}^{2n}\ -\ \underbrace{\sum_{n = 1}^{\infty}\pars{\half}^{2n}}_{\ds{1 \over 3}} \\ = &\ -\bracks{\Psi\pars{1 + z} + \gamma}_{\ z\ =\ -1/2} \\[3mm] & - \bracks{% {1 \over 2z} - \half\,\pi\cot\pars{\pi z} - {1 \over 1 - z^{2}} + 1 - \gamma - \Psi\pars{1 + z}}_{\ z\ =\ 1/2} - {1 \over 3} \\[8mm] = &\ -\Psi\pars{\half} - {2 \over 3}\ +\ \underbrace{\Psi\pars{3 \over 2}}_{\ds{\Psi\pars{1/2} + 1/\pars{1/2}}} - {1 \over 3} = \color{#f00}{1} \end{align}

$\Psi$ and $\gamma$ are the Digamma function and the Euler-Mascheroni constant, respectively. We used the Digamma Recurrence Formula $\ds{\Psi\pars{z + 1} = \Psi\pars{z} + 1/z}$ and the identities $\mathbf{6.3.14}$ and $\mathbf{6.3.15}$ in this link.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.